Pattern of Musculoskeletal Manifestation in Patient with Diabetes Mellitus (East West Medical College Journal, 2024)
Background: Diabetic mellitus (DM) both type 1 and type 2 increasing dramatically throughout worldwide. DM involved all the vital organs including musculoskeletal system. Objective: The purpose of study was to find out patterns of musculoskeletal manifestation (MSM) in diabetic patients & to find out a strategy to improve the outcome of the MS complications in patients with Diabetes Mellitus. Material and Methods: This was hospital based observational study conducted on 143 diabetics patients with musculoskeletal manifestations, both men and women (aged e”15- 70 years) visited in outpatient department and hospital admitted patient in a tertiary care of teaching hospital. Patterns were defined by a meticulous history, relevant general and systemic examination & with the aid of musculoskeletal (MS) Function Assessment semi structured Questionnaire. Results: MSM are common among patients with type 2 diabetes Out of 143 patients in our study 103(72.03%) were Male and 40(27.97%) were female, and male –female ratio 2.57:1. The age distribution of study patients was 15 to 70 years. Overall, 72.03.% of patients were among the 40-59 years old and about 20.28% were 60 years and mean age of the patients was 55±5. Above which is statistically significant (P= 0.048). The shoulder involvement as adhesive capsulitis (frozen shoulder) was found among 69(48.25%) on the diabetic cohort and statistically significant (P=